The effects of chitosan supplementation on anthropometric indicators of obesity, lipid and glycemic profiles, and appetite-regulated hormones in adolescents with overweight or obesity: a randomized, double-blind clinical trial - Somaye Fatahi; Ali Akbar Sayyari; Masoud Salehi; Majid Safa; Mohammadhassan Sohouli; Farzad Shidfar; Heitor O. Santos (BMC, 2022)
Abstract Background Chitosan is one of dietary fiber that has received great attention in improving obesity-related markers, but little is known on its effects on adolescents. Objectives To analyze the effects of chitosan supplementation on obesity-related cardiometabolic markers and appetite-related hormones in adolescents with overweight or obesity. Methods and analysis A randomized clinical trial was performed on 64 adolescents with overweight and obesity, who were randomly allocated to receive chitosan supplementation (n = 32) or placebo as control (n = 32) for 12 weeks. Anthropometric measures, lipid and glycemic profiles, and appetite-related hormones were examined. Results Sixty-one participants completed study (chitosan = 31, placebo = 30). Chitosan supplementation significantly improved anthropometric indicators of obesity (body weight: − 3.58 ± 2.17 kg, waist circumference: − 5.00 ± 3.11 cm, and body mass index: − 1.61 ± 0.99 kg/m2 and − 0.28 ± 0.19 Z-score), lipid (triglycerides: − 5.67 ± 9.24, total cholesterol: − 14.12 ± 13.34, LDL-C: − 7.18 ± 10.16, and HDL-C: 1.83 ± 4.64 mg/dL) and glycemic markers (insulin: − 5.51 ± 7.52 μIU/mL, fasting blood glucose: − 5.77 ± 6.93 mg/dL, and homeostasis model assessment of insulin resistance: − 0.24 ± 0.44), and appetite-related hormones (adiponectin: 1.69 ± 2.13 ng/dL, leptin − 19.40 ± 16.89, and neuropeptide Y: − 41.96 ± 79.34 ng/dL). When compared with the placebo group, chitosan supplementation had greater improvement in body weight, body mass index (kg/m2 and Z-score), waist circumference, as well as insulin, adiponectin, and leptin levels. Differences were significant according to P-value < 0.05. Conclusion Chitosan supplementation can improve cardiometabolic parameters (anthropometric indicators of obesity and lipid and glycemic markers) and appetite-related hormones (adiponectin, leptin, and NPY) in adolescents with overweight or obesity.